STRUKTUR KOMUNITAS MAKRO ALGA DI PESISIR PULAU KECAMATAN BULANG - Notowinarto Notowinarto; Ramses Ramses; Mulhairi Mulhairi (SIMBIOSA, 2014)
Bulang districts Batam Islands of  Riau province (Riau Islands), its consists of many islands with as well as having the potential diversity of coastal marine life in particular kinds of macro algae or seaweed. Conducted research aimed to determine the structure of macro- algal communities in the intertidal zone islands. The results of the identification of algal species found 16 species are: the Order of Chlorophyceae as 6 spesies; Order Phaeophyceae as 2 spesies; and Order Rhodophyceae as 8 spesies. The community structure at the five stations showed the highest values were found in the island of dominance Cicir (D ' = 0.79) , uniformity index values on Tengah Island (E ' = 0.99) , while the island Balak had the highest diversity index (H ' = 0.88) , with the abundance patterns of population structure on the island is pretty good Central . Results of correlation analysis of regression between IVI types of algae with the conditions of environmental quality suggests that there is a significance (Fhit ˃ F table and the value of r = 90 %) between IVI algae Halimeda sp and Cryptarachne polyglandulosa at each station with a temperature parameter surface (⁰C) , depth temperature (⁰C) and pH values. Keywords : Algae, Community Structure, Important Value Index.